2021
DOI: 10.1002/smll.202103400
|View full text |Cite
|
Sign up to set email alerts
|

Exciton‐Dominated Ultrafast Optical Response in Atomically Thin PtSe2

Abstract: semiconducting systems. [1,2] A representative example is layered 2D semiconductors, where reduced dielectric screening leads to huge exciton binding energies up to several hundreds of meV, enabling strong excitonic light-matter interactions even at room temperature. Thus, excitons in 2D materials govern fundamental optical properties such as light absorption and emission. [3,4] Furthermore, excitons in 2D systems often couple with their unique physical properties, such as a thickness-dependent change in the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 61 publications
5
20
0
Order By: Relevance
“…The overall sign of the differential reflection signal is negative, agreeing with a previous study . Considering that most of the differential transmission measurements on few-layer PtSe 2 have observed photoinduced bleaching (PB) over broadband ranges near the 800 nm probe wavelength, the observed negative sign of the differential reflection can be interpreted as PB. Note that PB has exhibited negative signs in differential reflection measurements of various 2D materials on transparent substrates, such as sapphire used in this work.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The overall sign of the differential reflection signal is negative, agreeing with a previous study . Considering that most of the differential transmission measurements on few-layer PtSe 2 have observed photoinduced bleaching (PB) over broadband ranges near the 800 nm probe wavelength, the observed negative sign of the differential reflection can be interpreted as PB. Note that PB has exhibited negative signs in differential reflection measurements of various 2D materials on transparent substrates, such as sapphire used in this work.…”
Section: Resultssupporting
confidence: 90%
“…Note that, while the previous study observed an additional standing wave CP mode in chemical vapor-deposited PtSe 2 , 44 it was not identified in our experiment, probably due to the relatively weak PtSe 2 − substrate coupling of the mechanically exfoliated flake sample 54,55 (see the extended discussion in the Supporting Information, Figure S3). The decaying background in the −ΔR/R 0 trace corresponds to the dynamics of the pumpgenerated carriers at the 800 nm probe wavelength, as demonstrated in previous studies 45,47,48,56 (see the extended discussion and associated broadband transient responses in the Supporting Information, Figure S4). The full −ΔR/R 0 trace can be modeled by the following function,…”
Section: ■ Results and Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…While the transport and catalytic properties of PtX 2 have been thoroughly investigated, its electronic excitation spectrum, including the collective excitations (excitons and plasmons), remains largely unexplored. Understanding these excitations is the key to controlling the optical properties of the material and for future photonic or optoelectronic applications. , The optical excitations in the MoX 2 and WX 2 semiconducting TMDs have been intensely studied during the past years because of the unique exciton physics found in their mono- and few-layer structures. , In comparison, the optical properties of few-layer PtX 2 have only recently gained attention, and only the most basic properties of their excitons have so far been addressed. The plasmon excitations of bulk and thin layers of PtTe 2 were reported by Ghosh et al However, in these measurements the samples were not atomically thin and substrate–sample interactions could not be ruled out. To date, the electronic excitation spectrum of freestanding few-layer PtX 2 remains unexplored, and it is unclear how it depends on the number of layers and the metal–semiconductor transition taking place as the thickness decreases to the monolayer limit.…”
mentioning
confidence: 99%